A critical assessment of watershed management in Indonesia : a thesis presented in partial fulfillment of the requirements for the degree of Master of Applied Science in Natural Resource Management at Massey University - Widyaningtyas, Novia (Massey University, 2005)
To address many environmental problems in Indonesia, the Ministry of Forestry created a planning system and developed guidelines to manage the watersheds in the country. Today, the environmental problems are still continuing, calling for improvement of watershed management. This study reviewed international guidelines, selected case studies of other countries' experiences, and the watershed management guidelines in Indonesia, then compared and contrasted the result of these reviews and made recommendations in order to improve watershed management and planning in Indonesia. The international guidelines published by ASEAN, FAO, ESCAP, UNEP, and ADB offered several frameworks of watershed management from various perspectives. The comparisons between these frameworks/perspectives and the Indonesian guidelines gave an opportunity to make an assessment and opened up the possibility of improving the existing framework and practice in Indonesia. The international guidelines provided some input on the importance of monitoring and evaluation in the management process, emphasised the need for adequate data for planning, and advocated an iterative process in planning. The assessment of the Indonesian guidelines and practice of water treatment management and planning: (1) proved ineffective, as demonstrated by the inconsistency and discontinuity of development, (2) was based on poor quantity and quality of data, (3) provided inadequate legal background, and (4) was implemented by an inadequate infrastructure. These problems created gaps that can be filled with recommended best practices learned from other developing countries (the Philippines, Malaysia, Thailand, and India). These recommendations include: (1) Establishment of an adequate national information system of watersheds and their management, (2) Improvement of the planning system, to be consistent with the planning hierarchy and to be iterative, (3) Promotion of collaboration and partnerships by the government, (4) Strengthening of the legal system as the foundation of effective watershed management and planning, and (5) Encouragement and strengthening of public participation in watershed management and planning.
Keywords: Watershed management; Indonesia